Development and testing of a nonradioactive DNA oligonucleotide probe that is specific for Vibrio cholerae cholera toxin. - Wright, A C (1992)
An alkaline phosphatase-labeled oligonucleotide DNA probe (CTAP) that was specific for the cholera toxin gene (ctxA) was identified. All cholera toxin-producing strains of Vibrio cholerae, regardless of serotype, hybridized with the CTAP probe, while nontoxigenic strains from either environmental sources or from deletion or substitution mutations did not hybridize. Unlike the whole-gene probes for either ctxA or for the heat-labile toxin or Escherichia coli (eltA), this 23-base sequence did not hybridize with E. coli or with vibrios other than V. cholerae that produce related toxins. By using CTAP to identify colonies grown on nonselective medium, V. cholerae was enumerated at concentrations of 10(3) to 10(7)/g from stool samples of volunteers who had ingested V. cholerae O1 strain 569B. CTAP provides a specific and sensitive tool for diagnosis and environmental monitoring of cholera toxin-producing V. cholerae.